PENGONTROLAN ALAT PENCAMPUR TEH MENGGUNAKAN ANDROID BERBASIS BLUETOOTH - Ahmad mungalim (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2016)
Introduction Technology bluetooth is many use for sector elektronika. Application for system introduction bluetooth is many in tool technology (example handphone) and a market commercial, handphone or smartphone that operation system android can donwload in playstore that can be install in handphone android. Essence smartphone this moment be an smartphone multyfunction can do service internet (WAP, GPRS, 3G, 4G) and have operation system self can do a use as control tool operasion system open souce have google. That give name ANDROID as control tools long distance (remot) its a use net bluetooth for control tools mixing tea. Method that make a software that a can aktive be software that alreadyinstall in handphone that use operation system android. Hardware equipped with module bluetooth HC-05 that use for communicated between hardware and software. Data to send for net bluetooth to mikrokontroler Atmega328P. Microcontroler play role as brain for device hardware. A between smartphone and device hardware eachs do pairing device to be able connected until between can communication.